Comparison of control methods for coccidiosis in native Spanish 'Castellana Negra' chikens - Miguel, J.A.=700 1 Asenjo, B.; Ciria, J.; Del cacho, E.; Calvo, J.L.
(En, Es)
Ilus., 22 ref.
Keywords: POLLO; EIMERIA; ENFERMEDADES DE LOS ANIMALES; CONTROL DE ENFERMEDADES; MONENSIMA; VACUNAS; ESPAÑA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH